The Effect of The Tree Rats (Rattus Tiomanicus (Miller, 1900)) Attack on The Quality of The Crude Palm Oil (CPO) Palm Oil (Elaeis Guineensis Jacq.) Plantations of Palangkaraya Central Kalimantan - Dasuki, Diva Rosa Nirwana; Nurcahyani, Nuning; Mumtazah, Dzul Fithria; Master, Jani (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2024)
Indonesia is the world’s largest producer of Crude Palm Oil (CPO). Tree rats (Rattus tiomanicus (Miller, 1900)) pose a significant problem in palm oil plantations by eating and damaging the mesocarp, reducing fruit weight, and affecting the Oil Extraction Rate (OER) and Free Fatty Acid (FFA) levels in CPO. This study investigates the impact of rat bites on CPO quality, focusing on OER and FFA levels. Using an experimental method, palm fruit groups with varying rat attack levels were compared to rested (3 days delayed in transport) and other pest attacked fruit groups. Results from a one-way ANOVA and Post Hoc LSD test showed that severe rat attacks (>50%) significantly affected OER and FFA compared to other conditions.